2018
DOI: 10.1093/ajae/aay091
|View full text |Cite
|
Sign up to set email alerts
|

Does Trade Policy Impact Food and Agriculture Global Value Chain Participation of Sub‐Saharan African Countries?

Abstract: The emergence of food and agriculture global value chains (GVCs) is challenging the way scholars look at trade data, as well as how policy makers establish their trade policies. The common perception is that Sub‐Saharan African (SSA) countries, unlike most Latin American and Asian countries, are not deeply integrated into global production networks. Consequently, it is believed that the border protection policies of the former may have a limited impact on GVC participation. This paper challenges this conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 48 publications
4
43
0
Order By: Relevance
“…Similar findings are reported by Balié et al. (2018). Using a structural gravity model where the dependent variable is trade in value added for agriculture and food sectors, they showed that bilateral trade policies are key determinants of both backward and forward GVC participation in the food sector and, to a lesser extent, in the agricultural sector.…”
Section: Globalization Of Value Chains and Political Economysupporting
confidence: 93%
See 1 more Smart Citation
“…Similar findings are reported by Balié et al. (2018). Using a structural gravity model where the dependent variable is trade in value added for agriculture and food sectors, they showed that bilateral trade policies are key determinants of both backward and forward GVC participation in the food sector and, to a lesser extent, in the agricultural sector.…”
Section: Globalization Of Value Chains and Political Economysupporting
confidence: 93%
“…First, GVCs’ forward and backward integration in the agricultural and food sectors, though lower on average than in the manufacturing sectors, has important variation across sectors (see Figure 2). Second, GVC integration has grown significantly in the last decades (Balié et al., 2018). Third, there is also significant variation across countries.…”
Section: Globalization Of Value Chains and Political Economymentioning
confidence: 99%
“…The results of this letter suggest that, as countries get more integrates through international trade, the absence of technological progress to offset the demand of land from population and income growth, would result in increased cropland expansion across the world. Such levels of integration are likely to increase as trade policies are implemented in order to satisfy regional increases in demand for crops as a result of biofuel production and income growth (Baldos and Hertel 2016) and greater participation of developing countries in global value chains (Maertens et al 2012, Balié et al 2018. Ready access to international markets may be an important mechanism to alleviate the supply fluctuations of a more variable climate (Baldos and Hertel 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Academic research on the agricultural industry value chain is mainly focused on participation model analysis [69,70], participation efficiency [71,72], measurement and development of value chain position [73,74], value chain financing model [75,76], and performance study of value chain participation [29,77]. The widely existing new agricultural business entities and social service organizations actively assist farmers in joining the agricultural value chain.…”
Section: Implication and Classification Of The Agricultural Value Chainmentioning
confidence: 99%